Cellular characteristics and milk component productivity of primary bovine mammary cells for cell-cultured milk component production - Hyuk Cheol Kwon; Hyun Su Jung; Do Hyun Kim; Jong Hyeon Han; Sung Gu Han (Journal of Animal Science and Technology)
Despite the increasing demand for milk, there is a simultaneous growth in awareness regarding sustainable dairy farming and concerns about environmental issues. The concept of generating milk components without traditional dairy farming has been introduced through the utilization of bovine mammary cells. However, the establishment of a robust primary bovine mammary alveolar cells for cell-cultured milk component production remains a challenge. Hence, the aim of this study was to assess the cellular attributes and milk component productivity of primary bovine mammary cells through various stages of cell subculture. The 1 cm3 pieces of mammary tissues were incubated onto a 10-cm cell culture dish until the cells grow out from the tissues. After the removal of mammary tissues, primary bovine mammary cells (fibroblasts, FBs; myoepithelial cells, MCs; epithelial cells, ECs) were isolated and purified through their different trypsin sensitivity. The primary bovine mammary cells were cultured with control culture media (CCM; without hormones) and differentiation culture media (DCM; with prolactin, insulin, cortisol, progesterone, 17b-estradiol, and epidermal growth factor). At passage 1, FBs, MCs, and ECs cultured with CCM displayed the highest levels of vimentin, α-smooth muscle actin, and cytokeratin 18/19 expression, respectively (p < 0.001). These cellular characteristics were not consistently maintained across subsequent passages, with a notable reduction in cell numbers (p < 0.001). At passage 1, ECs cultured in DCM exhibited higher milk component productivity in comparison to those cultured in CCM (p < 0.05). However, the synthesis of milk components exhibited a gradual decline as vacuoles increased in ECs throughout consecutive passaging. ECs cultured with CCM were unable to synthesize milk components due to the loss of tight junctions caused by matrix metalloproteinase activation. Conversely, ECs cultured with DCM boosted milk component production by intact tight junctions and low matrix metalloproteinase activity (p < 0.05). Our findings demonstrated the requirement for various hormones to maintain the productivity of primary bovine mammary cells over successive passages. These results highlight the importance of hormonal optimization to establish the stable primary cells in cell-cultured milk production.